Traffic related air pollution and its impact on respiratory health among children - Hisamuddin, Nur Hazirah; Jalaludin, Juliana (Universiti Putra Malaysia, 2019)
Exposure to traffic related air pollution (TRAP) is a public health concern particularly in children, who are one of the most susceptible groups of the population. Children are more vulnerable to such exposure by virtue of their increased susceptibility and the higher doses received. The materials for this review was obtained from several online databases ; PubMed, Proquest, Scopus, Springerlink and Science Direct (year 1990 to 2018). In this review, we emphasized several relevant studies on respiratory health effects among children living in the proximity to heavy traffic area and focus on the factors, which contributed to the severity of the health outcomes. Short term TRAP exposure reduces lung function, increases respiratory symptoms and incidence of asthma and allergic diseases especially for those who living within 75 m from the heavy traffic area. Preventive measures must be taken in order to protect children from exposure to traffic air pollutants.